Pharmacy services in primary healthcare facilities: A survey of patients’ perspectives and influence of demographic factors on satisfaction - Onah, Paul O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2026)
Background: The dispensing of medicines and other pharmacy services at primary health care (PHC) facilities is largely carried out by nurses, community health workers and pharmacy technicians. There are concerns about quality, as dispensary staff are often unqualified to perform pharmacy services. This study is therefore aimed at assessing satisfaction with medication-related services at PHCs. Methods: This survey study was carried out in ten selected PHCs located in Jere and Maiduguri metropolitan area councils of Borno State. A modified pharmaceutical service quality questionnaire (PSQ-18) was administered to randomly selected patients at dispensary units. Mean item and satisfaction domain scores were calculated and scores <3 (? 70%) was considered satisfaction. The chi-square test was used to determine the association between demographic factors and satisfaction. P values < 0.05 were statistically significant. Results: The dispensary staff consists of community health workers (58.6%), junior community health workers (18.4%) and pharmacy technicians (17.9%). Satisfaction was adequate for medicine information (88.3%), while quality of services (61.7%), medicine availability (47.6%), timeliness of services (45.1%) and good relationships with staff (30.4%) performed poorly. There was an insignificant association between satisfaction and demographic variables except for medicine availability (p<0.001). Conclusion: Satisfaction with medicine information was adequate; other aspects of services performed poorly. Demographic factors had no significant association with satisfaction, with the exception of medicine information. There is need to improve dispensary services if satisfaction is to be achieved among patients.